2010
DOI: 10.2174/1874325001004010067
|View full text |Cite
|
Sign up to set email alerts
|

Promising Clinical Results of the Universal Total Wrist Prosthesis in Rheumatoid Arthritis

Abstract: Abstract:The purpose of this study was to evaluate the results of the Universal Total Wrist prosthesis.Seventeen wrist arthroplasties were performed in 15 patients using the Universal Total Wrist prosthesis. The 11 women and 4 men in the study group ranged in age from 45 to 86 years. Fourteen patients had rheumatoid arthritis and one had osteoarthritis. Follow up ranged from 20 to 74 months. Patients were evaluated for range of motion, with the Disabilities of the Arm, Shoulder, and Hand (DASH) survey and radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…Total arthroplasty using a prosthesis gives superior functional results; their use is limited by the high rate of complications and failure [10][11][12][13][14][15][16][17]. New models of the prosthesis have recently been developed but still lack followup [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Total arthroplasty using a prosthesis gives superior functional results; their use is limited by the high rate of complications and failure [10][11][12][13][14][15][16][17]. New models of the prosthesis have recently been developed but still lack followup [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the meta-analysis for second-and third-generation implants, 7 this review added 8 new studies of fourth-generation implants, 6,8,9,12,13,16,22,23 3 new studies of third-generation implants, 14,15,17 and one long-term registry study. 18 TWA tends to fail earlier than hip or knee arthroplasties, but TWA has better short-term outcome.…”
Section: Discussionmentioning
confidence: 99%
“…14 of the studies reported pain relief, 6,[8][9][10][11][12][13]15,17,[19][20][21][22][23] but only 8 used validated scales, and the rest used ordinal scales, severity, and/or frequency to measure pain. Using the visual analogue scale (VAS) for pain, 2 studies reported improvement in the mean score from 8 to 2 (p<0.05) 9 and from 67 to 27 (p<0.001), 23 but one study reported no significant improvement.…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Winterswijk [12] demonstrated promising clinical results of this prosthesis in rheumatoid arthritis. All range of motion values improved after surgery with the average post-operative motion noted to be 29º of dorsiflexion, 38º volar flexion, 7º radial deviation and 17º ulnar deviation.…”
Section: Universal Total Wristmentioning
confidence: 95%